Impacto Social del Hospital Día Oncológico de la Ciudad de Encarnación (Journal on studies and research of academic knowledge, 2016)
In order to "determine the impact caused in the community of Encarnación with the "Oncological Day Hospital" (HDO), this research is an no experimental, quantitative and qualitative; descriptive research developed in the city of Encarnación. The analysis unit made up of directors of health care public institutions (4);medical oncologists (3); the first President of Fundación Lazos del Sur; HDO patients (28); community people diagnosed with cancer (32); people from different sectors of the community, including family members of people diagnosed with cancer (392); HDO neighbors (15). Open and closed questions were applied (surveys and interviews). In conclusion, the installation of the hospital in the region generates both qualitative positive change and quantitatively in the community for the promotion, prevention, diagnosis, treatment and research of oncological diseases through the management and multiple services with qualified professionals who offer their services with quality and warmth. It also allowed to gather information that will help reveal the prevalence of oncological diseases in the region and attention on HDO of Encarnación as well as other institutions, at the same time, it will contribute to draw up health policies for comprehensive care of patients with cancer in Itapúa.
Keywords: Cancer Day; Cancer; Social Impact; Hospital